Effects of different order of combined training on functional capacity, blood pressure, and body composition in women from 53 to 79 years old - Ágatha Graça; Higor Santos Fonseca; Fábio Luiz Cheche Pina; Rodrigo Garcia Fiorillo; Jerry Lawrence Mayhew; Aline Mendes Gerage; Daniel Vicentini de Oliveira; Matheus Amarante do Nascimento (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: To assess the effects of order of resistance training (RT) and high-intensity interval training (HIIT) on functional capacity, blood pressure, and body composition in middle-aged and older women. Methods: Twenty-two participants were randomly assigned to one of two groups: RT followed by HIIT (RT-HIIT, n = 10, mean age 64.5 ± 7.9 years) or HIIT followed by RT (HIIT-RT, n = 10, mean age 59.32 ± 4.44 years). Both groups trained twice a week for 8 weeks. RT was composed of 7 exercises for the upper and lower body. HIIT was composed of alternate pairings of high-intensity (> 85% of maximum heart rate [MHR]) and moderate-intensity (60% MHR) running. Results: A time effect was found for upper-body muscle endurance (HIIT-RT = +9.43%; RT-HIIT = +6.16%), agility and dynamic balance (HIIT-RT = -5.96%; RT-HIIT = -8.57%), and cardiorespiratory fitness (HIIT-RT = +5.14%; RT-HIIT = +6.13%), with no difference between groups. Body composition and blood pressure did not change throughout the investigation for either group. Conclusion: Eight weeks of a combined HIIT and RT exercise program improved functional capacity of middle-aged and older women without altering blood pressure and body composition, regardless of the order of exercises.